(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2013)
Research is systematic and objective analysis and recording of controlled observations that may lead to the development of generalizations, principles, or theories, resulting in prediction and possibly ultimate control of events (Best and Kahn, 1999). Research indicates ardent curiosity and fertile imagination. It is a attitude of scientific enquiry. Research is a systematic, controlled and empirical procedure to seek hidden facts emphasizing prior planning which envisages the quick and systematic pattern. Research needs sustained procedure, which engulfs lot of thinking and activities (Matheswaran, 2008). Research investigates ideas and uncovers useful knowledge. It is personally rewarding and socially beneficial. Most would accept that research is an essential component for a well-rounded academic culture in any higher education institution; it contributes extensively to knowledge bases and is good for the individual researcher’s profile, work satisfaction and career development. If utilised properly it should also be good for the employing institution’s profile and contribute, either indirectly or directly, to its income generation. Research has mainly five functions-analytical and explanatory, synoptic, evaluation, forward looking and advisory. The last two are important from the viewpoint of innovation and reform.